Synergistic interaction between the fibroblast growth factor and bone morphogenetic protein signaling pathways in lens cells - Boswell, Bruce A. (Mol Biol Cell, 2015)
Fibroblast growth factors (FGFs) play a central role in two processes essential for lens transparency—fiber cell differentiation and gap junction–mediated intercellular communication (GJIC). Using serum-free primary cultures of chick lens epithelial cells (DCDMLs), we investigated how the FGF and bone morphogenetic protein (BMP) signaling pathways positively cooperate to regulate lens development and function. We found that culturing DCDMLs for 6 d with the BMP blocker noggin inhibits the canonical FGF-to-ERK pathway upstream of FRS2 activation and also prevents FGF from stimulating FRS2- and ERK-independent gene expression, indicating that BMP signaling is required at the level of FGF receptors. Other experiments revealed a second type of BMP/FGF interaction by which FGF promotes expression of BMP target genes as well as of BMP4. Together these studies reveal a novel mode of cooperation between the FGF and BMP pathways in which BMP keeps lens cells in an optimally FGF-responsive state and, reciprocally, FGF enhances BMP-mediated gene expression. This interaction provides a mechanistic explanation for why disruption of either FGF or BMP signaling in the lens leads to defects in lens development and function.